Geometry, Charge Distribution, and Surface Speciation of Phosphate on Goethite - Rahnemaie, Rasoul; Hiemstra, Tjisse; van Riemsdijk, Willem H (Langmuir, 2007)
The surface speciation of phosphate has been evaluated with surface complexation modeling using an interfacial charge distribution (CD) approach based on ion adsorption and ordering of interfacial water. In the CD model, the charge of adsorbed ions is distributed over two electrostatic potentials in the double-layer profile. The CD is related to the structure of the surface complex. A new approach is followed in which the CD values of the various surface complexes have been calculated theoretically from the geometries of the surface complexes. Molecular orbital calculations based on density functional theory (MO/DFT) have been used to optimize the structure of a series of hydrated surface complexes of phosphate. These theoretical CD values are corrected for dipole orientation effects. Data analysis of the PO4 adsorption, applying the independently derived CD coefficients, resolves the presence of two dominant surface species. A nonprotonated bidentate (B) complex is dominant over a broad range of pH values at low loading (≤1.5 μmol/m2). For low pH and high loading, a strong contribution of a singly protonated monodentate (MH or MH−Na) complex is found, which differs from earlier interpretations. For the conditions studied, the doubly protonated bidentate (BH2) and monodentate (MH2) surface complexes and the nonprotonated monodentate (M) complex are not significant contributors. These findings are discussed qualitatively and quantitatively in relation to published experimental in-situ CIR−FTIR data and theoretical MO/DFT−IR information. The relative variation in the peak intensities as a function of pH and loading approximately agrees with the surface speciation calculated with the CD model. The model correctly predicts the proton co-adsorption of phosphate binding on goethite and the shift of the IEP at low phosphate loading (≤1.5 μmol/m2). At higher loading, it deviates.